Pembuatan Purwarupa Songket Pakaian Adat Silungkang di Kecamatan Silungkang Kota Sawahlunto Sumatera Barat (Studi Kasus: Pada Kerapatan Adat Nagari Silungkang Dan Kantor Disperindag Kota Sawahlunto) - Desman, Nurul Safira; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe process of making a Silungkang Songket prototype in Sawahlunto City uses a descriptive method with data collection techniques through interviews with traditional leaders and service offices. The process of making songket silungkang traditional clothing prototypes in Sawahlunto City is as follows: (1) data collection is done by interviewing techniques, (2) making a design in the form of a product to be made, (3) prototype making process in accordance with the work plan -the basic provisions of a topic that must be developed starting from making cover which is the hard skin on the outside of the book containing the title of the book, and accompanied by several supporting images; the preface contains a number of paragraphs which contain the thanksgiving of the author to Allah SWT and those who have helped and always support, a description of the prototype content, the basis and purpose of prototyping, the author's expectations, and the place, month and year when the preface was made ; the introduction contains a brief introduction to the Silungkang Songket and also a little about Sawahlunto City; the main contents of the book contain articles about silungkang songket which include history, motives and types based on the year.Keywords: silungkang songket, prototype